(untitled) (Revista da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo, 1976)
The applicability of the indexes substances chromic oxide and chromogens — to measure the fecal excretion, was studied in mares, 1/2 blood Breton breed and 1/2 Thoroughbreed. The animals were maintained in individuals boxes where received ration containing 0,136% of chromic oxide and 69,8 units of chromogens per gram of dry matter. The faeces were quantitatively collected in 12 hours intervals daily in order to obtain representative samples for 2Jf hours and 8 total days periods. The conventional, chromic oxide and chromogens methods showed, between breeds, statistically significant differences. The chromic oxide method differed significantly in relation to the total collection, while the estimated excretion through chromogen showed the best results when compared with the conventional method.